Public Engagement with the Criminal Justice System in the Age of Social Media - Michelle Katherine Larson Rose; Richard Logan Fox (Oñati Socio-Legal Series)
Exemplified by the landmark trial of O.J. Simpson, news media coverage of criminal cases in the United States is now regularly dominated by tabloid style coverage, complete with fixation on the victims and accused in criminal cases. Investigators have shown that such coverage of criminal proceedings is linked to decreasing levels of public trust and confidence in the criminal justice system. What is not yet understood is how rapid changes to the media universe in terms of online news sources and social networking are impacting coverage of criminal proceedings and public understanding of the criminal justice system. By surveying the American public on their news consumption habits, participation in social networking, knowledge and opinions of highly publicized criminal cases, and perceptions of the legitimacy of the justice system, we offer one of the first analyses of social media’s impact on public interaction with the criminal justice system. Ultimately we find little evidence that social media is enhancing citizen knowledge about or confidence in the criminal justice system, but we do uncover strong evidence that social media engagement with criminal trials leads to a greater desire for vengeance and encouragement of vigilante attitudes and behavior.